Archaeology of Precolumbian Florida - Milanich, Jerald T. (University Press of Florida, 1994)
This record of precolumbian Florida brings to life the 12,000-year story of the native American Indians who lived in the state. Using information gathered by archaeological investigations, many carried out since 1980, Jerald Milanich describes the indigenous cultures and explains why they developed as they did. In a richly illustrated book that will appeal to professional and avocational archaeologists, scholars, tourists, and local history buffs, Milanich introduces the material heritage of the first Floridians through the interpretation of artifacts and archaeological sites. Weaving together discoveries from such sites as the Lake Jackson mounds in the panhandle, Crystal River on the Gulf coast, and Granada on the Miami River, he relates the long histories of the native groups whose descendants were decimated during the European conquest of the sixteenth and seventeenth centuries.